Problems faced by students of ODL System in North India States - Chaudhary, Dr. Neelam (IJRDO-Journal of Applied Science, 2018)
This research study was conducted to find the problems faced by students of Open & Distance Learning System at their Graduate Level Study in North Indian States. The students living in remote and rural areas are already at the corner and are not having group discussions, any kind of debate related with their study in ODL system. What are their main problematic areas and where we should focus, here we tried to find out.